Бициллиеведение — новый исследовательский ландшафт в историографии Украины - Попова, Т. (Історіографічні дослідження в Україні, 2010)
В статье анализируется современное состояние бициллиеведения. Автор предлагает периодизацию истории изучения
творческого наследия П. М. Бицилли. В контексте общего
бициллиеведения рассмотрено состояние бициллиеведения в
историографии Украины. In the article the modern condition of Bicilli studies are analysed.
Author offers a division into periods of history of study of creative
legacy of P.M.Bicilli. In the context of general Bicilli studies the condition
of Bicilli studies of historiography of Ukraine is considered.
The article considers the intellectual biography and creative heritage
of P.Bicilly and analyses the trends of the studies in his life and
creative activity.